1999
DOI: 10.1002/(sici)1521-4141(199906)29:06<1972::aid-immu1972>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Protection against aerosol Mycobacterium tuberculosis infection using Mycobacterium bovis Bacillus Calmette Guérin-infected dendritic cells

Abstract: In the lung, dendritic cells (DC) are key antigen-presenting cells capable of triggering specific cellular responses to inhaled pathogens, and thus, they may be important in the initiation of an early response to mycobacterial infections. The ability of DC to enhance antigen presentation to naive T cells within the lungs was characterized with respect to Mycobacterium bovis Bacillus Calmette Guérin (BCG) vaccination against M. tuberculosis infection. In vitro derived DC were infected with BCG, which induced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 25 publications
5
87
0
3
Order By: Relevance
“…Human DC infected in vitro with M. tuberculosis or BCG undergo activation and maturation (13,21,22) that presumably enhance their potential to stimulate T cells. Also, murine DC infected with BCG and injected into the foot pad of mice can induce a specific T cell response and provide protection against a subsequent aerosol challenge with M. tuberculosis (23). These findings support the hypothesis that DC strengthen the cellular immune response against mycobacteria.…”
supporting
confidence: 72%
“…Human DC infected in vitro with M. tuberculosis or BCG undergo activation and maturation (13,21,22) that presumably enhance their potential to stimulate T cells. Also, murine DC infected with BCG and injected into the foot pad of mice can induce a specific T cell response and provide protection against a subsequent aerosol challenge with M. tuberculosis (23). These findings support the hypothesis that DC strengthen the cellular immune response against mycobacteria.…”
supporting
confidence: 72%
“…In contrast, macrophages are important for microbicidal function in the granuloma because they are more efficient in killing intracellular M. tuberculosis (17) and for sustaining Th1 polarity. In summary, the present study strongly positions the IL-12-secreting dendritic cell as the bridge between innate and adaptive immunities in TB, with important implications for dendritic cell-based vaccine design strategies (19,42).…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, infection of human DC with live bacillus Calmette-Guérin (20), M. tuberculosis (21), Listeria monocytogenes (9), Streptococcus gordonii (22), or Leishmania major (10) results in an increase in MHC and costimulatory molecule expression and enhanced T cell-stimulatory activity (20). Similar results were obtained with murine DC; these cells also demonstrated an enhanced ability to induce T cell responses in mice (23). In our studies, we found that the 19-kDa lipoprotein from M. tuberculosis, as well as synthetic lipopeptides, induced DC maturation.…”
Section: Figurementioning
confidence: 67%